A History and Ideology in the Development of the Writing of History Textbooks for High School in Indonesia 1994-2013 - Darmawan, Scopus ID: 57192940869, Wawan; Mulyana, Agus (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2020)
This article reveals the results of research on the contents of history subjects in history textbooks for High School that issued in two different government, those are the New Order Government and Reformation Government, which are considered to contain ideological messages. History textbooks that flowed from the curriculum follows on government policies. That wasn’t surprising if the government changed, they will change the curriculum, and also change the content of text books, in this case includes the history text books. The change indicates that history text books cannot be separated from the interests of the government’s ideology. The aim of this research is wanting to reveal the forms of ideology that is present in the content of history text books. The method that used is critical discourse analysis to know the ideological discourse in history text books from two different government periods. The history text books that are examined based on the 1994 Curriculum and the 2013 Curriculum to indicate two curriculums results from two reigns. Based on the results of this research, it can be compared with the ideology of writing content of history text books in the New Order and Reformation period, there are includes communism and Pancasila, deceit democracy and freedom for democracy, militarism and anti-militarism, neoliberalism and anti-communism, liberalism and anti-liberalism. However, there is still a single narrative of the nation in the New Order that could not be replaced by the Reformation era.